Studies on Hydrocarbons of Bombyx mori L - Tsuda, Kyosuke; Akaike, Eiko; Ikekawa, Nobuo; Suzuki, Mieko (Chemical & pharmaceutical bulletin, 1966)
The chemical structure of hydrocarbons in the silkworm was shown as comparing with that in the mulberry leaf by means of gas chromatographic technique and mass spectrometry. The hydrocarbons from both the silkworm and mulberry leaf consisted of a mixture of odd-and even-numbered carbons and major hydrocarbons in the wings were C34 to C36 those in both blood and larva, C21 to C27, and those in mulberry leaf, C16 to C20. Large hydrocarbons, C32, C34, C38, C40 and C41, were found in the wings.